Commitment to Organizations Viewed from Transformational Leadership and Work Satisfaction (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2018)
This study aims to determine the relationship between Transformational Leadership and Job Satisfaction with Commitment to the Organization. The sample chosen was 240 teachers, with the criteria of Private Junior High School Teachers in Bogor Regency. This study uses a Mixed Method Sequential Explanatory. The results of this study conclude that: a. There is a very significant positive relationship between Transformational Leadership and Commitment to the Organization as indicated by the correlation coefficient (ry1) = 0.505 and the coefficient of determination worth (ry1)2 = 0.255 which means Transformational Leadership contributes to 25.5% commitment to the organization. b. There is a very significant positive relationship between Job Satisfaction and Commitment to the Organization as indicated by the correlation coefficient (ry2) = 0.618 and the determination coefficient of (ry2)2 = 0.381 which means Job Satisfaction contributes to the Commitment to the Organization of 38.1%. c. There is a very significant positive relationship between Transformational Leadership and Job Satisfaction with Commitment to the Organization as indicated by the correlation coefficient (ry12) = 0.622 and the coefficient of determination (ry12)2 = 0.387 which means Transformational Leadership and Job Satisfaction contribute to the Commitment to the Organization as big as 38.7%.